Examining covert and explicit mechanisms of education inequity to foster just public education and authentic democracies: Special issue commentary - Wilson, Camille M. (Education Policy Analysis Archives, 2022)
In this editorial essay, the author pinpoints key insights, implications, and cross cutting themes that emerged from this special issue. These insights shed light on the interlocking connection between inequitable public education systems and vulnerable democracies, both of which fail to uphold their charge to be inclusive and just. Special attention is given to the harm of race-avoidant, classist, and/or public-aversive discourse and policies, the coopting of equity-oriented agendas for private interests, political underrepresentation, and the multifaceted reach of global neoliberalism. All of these factors exacerbate racial and socioeconomic disparities in education and society. The author emphasizes how these and other dynamics amount to the provision of educational equity being constrained by dominant logics of fear, scarcity, and competition; the racialization and privatization of public education access; and ultimately, the operation of elitist versus truly representative democracies. She builds upon the volume’s critical policy studies to stress the urgency of countering both covert and explicitly biased educational policy mechanisms in order to improve public education and construct more authentic democratic societies.